ANALISIS DESKRIPSI PENGGUNA FINTECH MODEL E-MONEY GOPAY GOJEK DI PURWOKERTO - Ria Manurung (LPPM Politeknik Saint Paul Sorong, 2020)
The purpose of the study was to descriptively identify FinTech users with the E-Money model on Go-Pay Gojek in Purwokerto. The research benefit is to find out the characteristics of FinTech users with the E-Money model on Go-Pay Gojek in the city of Purwokerto. This type of research is field research with qualitative data analysis methods. Types of data are primary and secondary data with data collection methods through questionnaires and interviews with respondents. The sampling technique is nonprobability with the selection of respondents based on the judgment of the researchers themselves with the sample criteria being Go-Pay users. The sampling method used was convenience due to the limited ability of the researcher. The data to be studied are 110 offline. The research was conducted in 4 districts in Banyumas Regency. Data processing activities include the stages of editing, compiling, calculating and tabulating data. The results of data processing explain that the people of Purwokerto City have recognized and used the FinTech Go-Pay “Gojek” with the E-Money model with a tendency to use the payment system with the E-Money model instead of cash. E-Money Go-Pay is in great demand by people in the city of Purwokerto as a transit city for millennials where residents tend to be immigrants both to study and work.